2020
DOI: 10.1093/gbe/evaa107
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Loss of abaA, a Master Regulator of Asexual Development in Filamentous Fungi, Correlates with Changes in Genomic and Morphological Traits

Abstract: Gene regulatory networks (GRNs) drive developmental and cellular differentiation, and variation in their architectures gives rise to morphological diversity. Pioneering studies in Aspergillus fungi, coupled with subsequent work in other filamentous fungi, have shown that the GRN governed by the BrlA, AbaA, and WetA proteins controls the development of the asexual fruiting body, or conidiophore. A specific aspect of conidiophore development is the production of phialides, conidiophore structures that are under … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
(59 reference statements)
0
19
0
Order By: Relevance
“…However, there is no available report on the biological function of Cti6 in the filamentous fungi until now. (Sewall, 1994;Mead et al, 2020). By deletion of PHD and Atrophin-1 domain, it was found that, similar to Δcti6, the fungal colony size, mycelial density and conidiation state of PHD domain deletion strain (cti6 ΔPHD ) on both PDA media and crop kernels were significantly restrained compared to the Ctrl fungal strain, but Atrophin-1 domain was only involved in the sporulation of the fungus (Figure 2 and 5).…”
Section: Discussionmentioning
confidence: 90%
“…However, there is no available report on the biological function of Cti6 in the filamentous fungi until now. (Sewall, 1994;Mead et al, 2020). By deletion of PHD and Atrophin-1 domain, it was found that, similar to Δcti6, the fungal colony size, mycelial density and conidiation state of PHD domain deletion strain (cti6 ΔPHD ) on both PDA media and crop kernels were significantly restrained compared to the Ctrl fungal strain, but Atrophin-1 domain was only involved in the sporulation of the fungus (Figure 2 and 5).…”
Section: Discussionmentioning
confidence: 90%
“…Knowledge gained can be extended to other fungal systems. Recently, new experimental approaches have been developed, focusing on the expression of genes encoding regulators of A. nidulans asexual reproduction with the aim of modifying developmental patterns of species such as Monascus ruber or Histoplasma capsulatum [12,86]. Although the trials were unable to trigger major morphological changes, they paved the way for the establishment of simple and reliable approaches for the experimental study of GRN rewiring and its consequences for organism evolution.…”
Section: Discussion How Grns Evolve and What Fungi Can Teach Us About The Processmentioning
confidence: 99%
“…Knowledge thus gained can, of course, be extended to other fungal systems. Recently, new experimental approaches have been developed, focused on the expression of genes encoding regulators of A. nidulans asexual reproduction with the aim of modifying developmental patterns of species such as Monascus ruber or Histoplasma capsulatum [12, 88]. Although the trials were unable to trigger major morphological changes, they paved the way for the establishment of simple and reliable approaches for the experimental study of GRN rewiring and its consequences on organism evolution.…”
Section: Discussionmentioning
confidence: 99%